PROBLEMATIKA DAN PEMBERANTASAN KORUPSI DI INDONESIA - Muallifin, M. Darin Arif (IAIN Tulungagung, 2015)
This article discusses various issues related to the practices ofcorruption. Corruption is nothing new and nothing to do with thelaw of halal and haram. It exists long time ago and make adjustmentsuccessfully to any changes of the rule in the country. In short,corruption is part of the country’s culture. In this case, corruptionincludes the practices of bribery, manipulation, and any practicesharmful to the country. Corruption is categorized as systemic crimewhich must be eradicated systematically. In the field of Law there is atheory of Legal System by Lawrence M. Friedman proposed to solvethe problem of corruption including legal substance, legal structure,and legal culture.Kata kunci: Problematika Korupsi, Pemberantasan, Peran KPK,Peran Masyarakat